PELAKSANAAN PROGRAM IMUNISASI DASAR LENGKAP (IDL) DI WILAYAH KERJA PUSKESMAS SUNGAI SALAK - Gusliati, Gusliati; Yunita, Jasrida; Dewi, Oktavia; Susmaneli, Herlina; Hanafi, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Immunization programs include efforts to reduce morbidity, mortality and mortality rates in infants and toddlers. This program is carried out for diseases that can be prevented by immunization such as tuberculosis, diphtheria, tetanus, hepatitis B, polio, measles, rubella, inflammation of the lining of the brain and pneumonia. Based on the Health Profile of the Sungai Salak Health Center in 2021, the achievement of complete basic immunization is 13.4% of the target of 95%. The purpose of the study was to analyze the Implementation of the Complete Basic Immunization Program (IDL) in the Working Area of the Sungai Salak Health Center, Indragiri Hilir Regency. This type of research is qualitative, descriptive, with a case study design. The research location is in the Working Area of the Sungai Salak Health Center, Indragiri Hilir Regency. The research time is August 2023. There were 6 informants for this research, consisting of 1 Main Informant, 2 Key, and 3 Supporting Informants. Data collection was conducted through in-depth interviews, observations and document review. Data validity is done by triangulation of sources, methods, and data. The results of this study found that human resources were still lacking because there were no logistics management personnel, the distance to immunization services was difficult, the low knowledge of mothers and families on the importance of immunization, and there was no monitoring so that the reporting of Complete Basic Immunization coverage was gaped. It is expected that the Head of the Puskesmas will form an immunization program energy team, in collaboration with Cross Sectoral to run the My Home My Vilage (MYMV) Program.Keywords: Complete Basic Immunization, Sungai Salak Health Center, and Immunization Program